Role of Notch and achaete-scute complex in the expression of Enhancer of split bHLH proteins. - Jennings, B.; de Celis, J.F.; Delidakis, C.; Preiss, A.; Bray, S. (Development, 1995)
The proteins encoded by Notch and the Enhancer of split complex are components of a cell-cell interaction mechanism which is important in many cell fate decisions throughout development. One such decision is the formation of the sensory organ precursor cell during the development of the peripheral nervous system in Drosophila. Cells acquire the potential to be neural through the expression of the proneural genes, and the Notch pathway is required to limit neural fate to a single cell from a proneural cluster. However, despite extensive analysis, the precise pathways linking the proneural with Notch and Enhancer of split gene functions remain obscure. For example, it has been suggested that achaete-scute complex proteins directly activate Enhancer of split genes leaving the action of Notch in the pathway unclear. Using monoclonal antibodies that recognise products of the Enhancer of split complex, we show that these proteins accumulate in the cells surrounding the developing sensory organ precursor cell and that their expression is dependent on the activity of Notch and does not directly correlate with expression of Achaete. We further clarify the pathway by showing that ubiquitous expression of an activated Notch receptor leads to widespread accumulation of Enhancer of split proteins even in the absence of achaete-scute complex proteins. Thus Enhancer of split protein expression in response to Notch activity does not require achaete-scute complex proteins.